2022
DOI: 10.2174/0929867328666210726094955
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products with Tandem Anti-inflammatory, Immunomodulatory and Anti-SARS-CoV/2 Effects: A Drug Discovery Perspective against SARS-CoV-2

Abstract: Background: COVID-19 is still causing victims with long-term health consequences, mass deaths, and collapsing healthcare systems around the world. The disease has no efficient drugs. However, previous studies revealed that SARS-CoV-2 and SARS-CoV have 96% and 86.5% similarities in cysteine proteases (3CLpro) and papain-like protease (PLpro) sequences, respectively. This resemblance could be significant in the search for drug candidates with antiviral effects against SARS-CoV-2. Objective: This paper is a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 190 publications
1
6
0
Order By: Relevance
“…Chalcone‐derived compounds have attracted much interest not only for their simple synthesis but also for their broad pharmacological properties. As reported in previous studies, synthetic chalcones showed promising inhibitory effects against cruzain, a cysteine protease of Trypanosoma cruzi [8] . Natural alkylated chalcones namely isobavachalcone, 4‐hydroxyderricin, xanthoangelol, xanthoangelol F, xanthoangelol D, xanthoangelol E, xanthoangelol B, xanthoangelol G, and xanthokeistal A showed strong to moderate inhibition of SARS‐CoV 3CL pro by impairing its cis‐ cleavage activity [7,9] .…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Chalcone‐derived compounds have attracted much interest not only for their simple synthesis but also for their broad pharmacological properties. As reported in previous studies, synthetic chalcones showed promising inhibitory effects against cruzain, a cysteine protease of Trypanosoma cruzi [8] . Natural alkylated chalcones namely isobavachalcone, 4‐hydroxyderricin, xanthoangelol, xanthoangelol F, xanthoangelol D, xanthoangelol E, xanthoangelol B, xanthoangelol G, and xanthokeistal A showed strong to moderate inhibition of SARS‐CoV 3CL pro by impairing its cis‐ cleavage activity [7,9] .…”
Section: Introductionsupporting
confidence: 66%
“…Among the studied compounds, chalcones represent one of the most investigated for the inhibition of cysteine proteases. It is a naturally occurring family that contains a scaffold of 1,3‐diaryl‐2‐propen‐1‐one [7,8] . Chalcone‐derived compounds have attracted much interest not only for their simple synthesis but also for their broad pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, four HCV protease inhibitor drugs, Simeprevir, Vaniprevir, Paritaprevir, and Grazoprevir with remdesivir inhibit the SARS CoV-2 PL pro [81] . One study showed that Amentoflavone, Rubranoside B, Savinin, Psoralidin, Hirsutenone, and Papyriflavonol A are good drug candidate for the search of antibiotics against PL pro and M pro [82] . Nine natural biflavones were also confirmed to be effective PL pro inhibitors with IC50 values ranging from 9.5 to 43.2 μM via anti-proteolytic activity determination [83] …”
Section: Discussionmentioning
confidence: 99%
“…Besides the above common flavones, amentoflavone, a hydroxyflavone and bioflavonoid, also has shown binding affinity with M pro , RdRp, NSP13, NSP15, and ACE2 in several in silico surveys. 349 – 351 Similar to flavanols, the hydroxy groups of flavones can be glycosylated, thus forming flavone glycosides. Baicalin, a 7-O-glucuronide of baicalein, is a biologically active flavonoid of natural origin obtained primarily from the roots of Scutellaria baicalensis Georgi.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%